'If You Do Not Write, You Dry Up': Tensions in Teacher Educator Research and Academic Writing - Nikki Aharonian; Orna Schatz Oppenheimer (MDPI AG, 2024)
Teacher educators struggle to balance heavy teaching loads, research, writing, and institutional service. This qualitative study uses institutional ethnography to question how college leadership understand the significance of academic scholarship in the professional lives of college-based teacher educators in Israel. Data from interviews with eight college position holders shed light on the working lives of college-based teacher educators and how they are positioned as researcher-writers in an institution where scholarship expectations are blurry. Findings reveal three themes: the importance of academic activity for institutional prosperity, the difficulties in academic scholarship experienced by teacher educators, and the support the institution provides to encourage and maintain academic activity. The discussion contemplates the tensions between institutional and individual teacher educator advancement. The complexity of the institutional structure deserves attention to achieve institutional aims and attend to individual faculty's professional needs and desires. The implications of this study are significant for leadership in teacher education and higher education around the world, prompting leaders to rethink ways of supporting faculty involved in research and writing alongside teaching and additional roles. Balancing conflicting roles, providing clear expectations, and maintaining an ongoing dialogue between teacher educators and leadership regarding professional development needs can lead to institutional prosperity alongside individual professional advancement.